Cytokinin Production by Azospirillum brasilense Contributes to Increase in Growth, Yield, Antioxidant, and Physiological Systems of Wheat (Triticum aestivum L.) - Zaheer, Muhammad Saqlain; Ali, Hafiz Haider; Iqbal, Muhammad Arslan; Erinle, Kehinde O.; Javed, Talha; Iqbal, Javaid; Hashmi, Makhdoom Ibad Ullah; Mumtaz, Muhammad Zahid; Salama, Ehab A. A.; Kalaji, Hazem M.; Wróbel, Jacek; Dessoky, Eldessoky S. (Frontiers in Microbiology, 2022)
Plant growth-promoting rhizobacteria are known to associate with several cereal crops. The rhizobacterium exerts its function by synthesizing diverse arrays of phytohormones, such as cytokinin (Ck). However, it is difficult to determine the plant growth promotion when a bacterium produces many different kinds of phytohormones. Therefore, to assess the involvement of Ck in growth promotion and activation of antioxidant and physiological systems, we set up this experiment. Wheat seeds (Triticum aestivum L.) were inoculated with Azospirillum brasilense RA−17 (which produces zeatin type Ck) and RA−18 (which failed to produce Ck). Results showed that seed inoculation with RA−17 significantly improved growth and yield-related parameters compared with RA−18. The activity of enzymes, proline contents, and endogenous hormonal levels in wheat kernels were improved considerably with RA−17 than with RA−18. Strain RA−17 enhanced grain assimilation more than strain RA−18 resulting in a higher crop yield. These results suggest that microbial Ck production may be necessary for stimulating plant growth promotion and activating antioxidant and physiological systems in wheat.